Regulatory differences in crop protection systems for soybean production: implications of the EU–Mercosur trade agreement - Strażyński, Przemysław; Korbas, Marek; Danielewicz, Jakub; Jajor, Ewa; Horoszkiewicz, Joanna; Mrówczyński, Marek; Marcinkowska, Katarzyna; Kierzek, Roman; Flaszka, Małgorzata (Journal of Plant Protection Research, 2026)
The political conclusion of the EU–Mercosur Partnership Agreement in December 2024 marks a significant shift in global agri-food trade and raises fundamental questions on regulatory coherence in plant protection. This study provides a comprehensive comparative assessment of crop protection systems in soybean (Glycine max L.) production between the European Union (represented by Poland) and Mercosur countries. Soybean was selected due to its strategic importance in global feed supply chains, the EU’s structural import dependence, and the crop’s high reliance on chemical and biological plant protection products (PPPs). The analysis reveals pronounced asymmetries in the availability of authorized active substances. Mercosur producers have access to 96 herbicide active substances compared to 16 in Poland (ratio 6 : 1); 96 chemical fungicide active substances compared to 5 (19 : 1); and 94 chemical insecticide active substances compared to only 2 (47 : 1). The disparity is particularly striking for biological fungicides, where 104 microbial strains are registered in Mercosur versus 2 in Poland (52 : 1). Even in biological insecticides, the ratio remains 3 : 1 (9 vs. 3). Approximately 100 active substances used in Mercosur soybean production are not approved in the EU. Pesticide application intensity in Brazil (12.63 kg a.s./ha) is 4.7 times higher than the EU average and over seven times higher than in Poland. In parallel, Maximum Residue Limits (MRLs) for selected substances differ substantially, in extreme cases by up to 200-fold. These quantitative asymmetries translate into divergent pest management capacity, resistance management flexibility, and production resilience. While the EU regulatory framework reflects a precautionary approach with progressive restriction of active substances, Mercosur systems operate with substantially broader chemical and biological portfolios enabling diversified and rotation-based control strategies. The findings demonstrate that regulatory differences – ranging from 6 : 1 to 52 : 1 depending on product category – constitute a structural factor shaping competitiveness, resistance risk, and food safety governance under the evolving EU–Mercosur trade framework.